Minat Olahraga di Kalangan Mahasiswa Universitas Pamulang - Sifa Nur Fauziah; Krisna Anggara; Zayana Rahmawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Interest in sports among students plays an important role in maintaining physical and mental health and improving the balance between academic activities and physical activity. This study aims to analyze the interest of Pamulang University students in sports and the factors that influence it. The method used in this study was a quantitative descriptive survey by distributing questionnaires to 100 students from various faculties at Pamulang University. The results showed that the majority of students had a fairly high interest in sports, especially sports such as running, badminton, and football. The main factors that influence this interest are awareness of the importance of health, and support from the social environment. However, there are several obstacles that are also identified, such as time constraints due to busy academic activities and lack of promotion of campus sports activities. This study suggests that universities improve sports facilities and provide programs that can motivate students to be more active in exercising regularly. Thus, it is hoped that students' interest and participation in sports can increase, which will ultimately have a positive impact on their quality of life and academic achievement.